Enzymatic Synthesis of Diacylglycerol-Enriched Oil by Two-Step Vacuum-Mediated Conversion of Fatty Acid Ethyl Ester and Fatty Acid From Soy Sauce By-Product Oil as Lipid-Lowering Functional Oil - Feng, Konglong; Fang, Huaiyi; Liu, Guo; Dai, Weijie; Song, Mingyue; Fu, Jiangyan; Wen, Linfeng; Kan, Qixin; Chen, Yunjiao; Li, Yuanyou; Huang, Qingrong; Cao, Yong (Frontiers in Nutrition, 2022)
Soy sauce by-product oil (SSBO), a by-product of the soy sauce production process, is lack to utilize due to an abundance of free fatty acid (FFA) and fatty acid ethyl ester (EE). Utilization of low-cost SSBO for production of value-added diacylglycerol (DAG)-enriched oil and its applications are promising for the sustainability of oil industry. The objective of this study was to utilize SSBO containing a high content of EE and FFA as raw material to synthesize DAG-enriched oil and to evaluate its nutritional properties in fish. Based on different behaviours between the glycerolysis of EE and the esterification of FFA in one-pot enzymatic catalysis, a two-step vacuum-mediated conversion was developed for the maximum conversions of EE and FFA to DAG. After optimization, the maximum DAG yield (66.76%) and EE and FFA conversions (96% and 93%, respectively) were obtained under the following optimized conditions: lipase loading 3%, temperature 38 ℃, substrate molar ratio (glycerol/FFA and EE) 21:40, a vacuum combination of 566 mmHg within the initial 10 h and 47 mmHg from the 10th to 14th hour. Further nutritional study in fish suggested that the consumption of DAG-enriched oil was safe and served as a functional oil to lower lipid levels in serum and liver, decrease lipid accumulation and increase protein content in body and muscle tissues, and change fatty acid composition in muscle tissues. Overall, these findings were vital for the effective utilization of SSBO resources and the development of future applications for DAG-enriched oil as lipid-lowering functional oil in food.